Big Marsh : The Story of a Lost Landscape - Register, Cheri, 1945- (Book collections on Project MUSE., 2016)
"An environmental history of Freeborn County, Minnesota's Big Marsh, which was tilled and drained 130 years ago at public expense for agricultural purposes. Told from a personal point of view, this story shows the enduring value of wild places and the importance of the fight to preserve them, both then and now"--